Analisis Tipologi Variabel Strategis pada Pengembangan Kawasan Ekowisata Kedung Ombo - Nafiah Ariyani; Akhmad Fauzi (Jurnal Wilayah dan Lingkungan, 2019)
The Kedung Ombo Reservoir area, which is rich in natural resources, has the potential to be developed as an ecotourism area, but institutional issues and policy focus bias have hampered its development. This study aims to identify strategic variables in the region and find a description of the interdependent relationship between these variables, which is useful in determining the right policy. Research data were obtained through focus group discussions and workshops. Data analysis using Micmac method. The results of the study determine 31 (thirty one) strategic variables in the development of the Kedung Ombo ecotourism area which are grouped into typologies as follows: (1) determinant variables, consisting of: special regulations and permits; (2) relay variable, consisting of: community involvement, tourism business potential, infrastructure readiness, tourism awareness, transportation, tourists, tourist attractions, accommodation, tourism promotion, tourism services, private investment, governance, coordination, role of apparatus and information; (3) autonomous variables, consisting of: local entrepreneurial abilities, developer's understanding of local norms, natural beauty, environmental carrying capacity, and accessibility; and (4) dependent variables such as: tax income, retribution income, availability of funds for the community, preservation of local wisdom, expansion of employment opportunities, conservation of reservoir functions, forest preservation, welfare improvement, and poverty reduction. This research also produces a sequence of priority scales of these strategic variables which is very useful for policy makers in directing the focus of policies to ensure the successful development of the Kedung Ombo ecotourism in a sustainable manner.